2017
DOI: 10.1189/jlb.5mr0217-059rr
|View full text |Cite
|
Sign up to set email alerts
|

Targeting C-type lectin receptors: a high-carbohydrate diet for dendritic cells to improve cancer vaccines

Abstract: Review of in vivo targeting of tumor antigens to lectin receptors on antigen-presenting cells using antibodies or ligands may improve the antitumor efficacy of vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 283 publications
(341 reference statements)
1
69
0
Order By: Relevance
“…N-bromosuccinimide (10 g, 55 mmol, 0.48 equiv.) was added and the reaction was stirred for 3 hours, after which the reaction was quenched with an aqueous solution of Na 2…”
Section: -(α-L-rhamnosyl)-1-propene (7)mentioning
confidence: 99%
See 2 more Smart Citations
“…N-bromosuccinimide (10 g, 55 mmol, 0.48 equiv.) was added and the reaction was stirred for 3 hours, after which the reaction was quenched with an aqueous solution of Na 2…”
Section: -(α-L-rhamnosyl)-1-propene (7)mentioning
confidence: 99%
“…In innate immunity, they promote the secretion of cytokines and in adaptive immunity, they contribute to endocytosis. [1,2] Examples of these receptors are DC-SIGN and the mannose receptor, both C-type lectins that are present on dendritic cells. Since the binding interactions between lectins and their carbohydrate-binding partners are often relatively weak, strong interactions depend on the multivalent binding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the ability to specifically target vaccine formulations to APC via CLRs, such as DC-SIGN and the mannose receptor, which recognize specific carbohydrate structures, is an option 26 . Targeting vaccines can be created by coupling of carbohydrates to antigen specific vaccine particles.…”
Section: For Anti-tumor Immune Responses the Induction Of Cytotoxic mentioning
confidence: 99%
“…immune memory and specific antibodies against the pathogen-associated antigens [3,[6][7][8][9][10][11]. Previous studies have demonstrated that in vivo targeting of professional APCs can be successfully achieved by using cell-specific receptors including C-type lectin receptors (CLRs) [12][13][14][15][16][17], mannose receptor (MR; CD206) [18][19][20]. In particular, CLRs are pattern recognition receptors (PRRs) that bind the carbohydrates moieties (e.g.…”
Section: Introductionmentioning
confidence: 99%